Mental health of the emergency sector nursing team (Research, Society and Development, 2022)
This study aims to identify in the scientific literature the mental disorders related to the work performed by the nursing team in the emergency sector. The research was carried out through studies available in the Virtual Health Library (BVS-BIREME), data from the Latin American and Caribbean Health Sciences Literature (LILACS) and the Scientific Electronic Library Online portal (SCIELO). The research took place from November 2021 to January 2022. The articles were written in Portuguese and published between the last ten years (2011 to 2021). Seven articles that met the inclusion criteria were analyzed and selected and grouped into two categories: studies focusing on common mental disorders related to the work of the nursing team in the emergency sector, studies focusing on risk factors for mental disorders in professionals in the nursing. A high prevalence of mental disorders in professionals in the nursing team in the emergency sector was evidenced in the studies. The pressures suffered by nursing professionals in the work environment contribute to removal due to mental disorders. By identifying risk factors for the development of mental disorders in nursing professionals, it is expected to find ways to intervene in order to reduce this type of exposure.